Analisis Perlakuan Akuntansi Produk Cacat Pada UD Batu Permai Junior Kecamatan Gambiran Banyuwangi - Novianti, Lailya; Sedyati, Retna Ngesti; Tiara, Tiara (Journal of Economic Education and Entrepreneurship, 2024)
This research aims to analyze the accounting treatment of defective products at UD Batu Permai Junior, Gambiran Banyuwangi District. This research is a type of descriptive research combined with quantitative research. The data collection method used to determine the accounting treatment of defective brick products and determine the cost of production at UD Batu Permai Junior uses interview, observation and document methods. Data analysis in this research uses descriptive analysis with a quantitative approach. The results of the research show that the treatment of defective products at UD Batu Permai Junior, Gambiran Banyuwangi District, is selling defective products that are still salable. Proceeds from sales of defective products are recognized as other income, without reducing overall production costs. Having defective products that are still sold reduces the losses experienced by the company. The average number of defective products in December 2023 is approximately 5%. The income received by UD Batu Permai Junior experienced a decrease due to the presence of defective products, if there where no defective brick products then the income obtained would be IDR. 129,521,000. After there is a defective product, the income obtained is IDR. 125,815,000, so there is a difference of Rp. 3,706,000, wich causes the company not to obtain optimal profits.